(untitled) (Revista Espacio Regional, 2021)
Studies about the agrofood global system have demonstrated how it have been responsable for the economic concentration among agrofood activities and practised particular pression above peasantry, compromising the autonomy and conditions that secure its social reprodution. In conraposition to this reality, arises the proposal of agroecology, as an alternative form of production and organization of agrofood activities. The Rede Ecovida de Agroecologia articulates ecological peasant’s groups, NGOs and consumers in Brazil’s southern States. This present research is based in the analisis of six commercial iniciatives of Rede Ecovida. The analisis realised allowed the observation that the construction of alternative mechanisms of markets have possibilited the organization of economic’s actions in a way that allows reconstruct and reinforce the peasant’s socioeconomical rationality, which is based in different principles from capitalism and in the search for the environmental sustainability. These markets, known as ’short circuits’, focus in the peasant-consumer’s approximation, favouring the social mediation and the market’s transparency, as well as the information’s circulation and trade. It is proposed an expanded approach about the ’short circuits’ idea, which, beyond the geographic proximity, considers aspects linked to the food access democratization and the social and cultural proximity of the agents envolved. From the notion of ’Circuits of Proximity’, it is indicated the idea of market’s construction which priorize the spacial proximity joint to the interpersonal information, to the strengthen of sociabilities, as well as to the reciprocity ans solidarity relations among the envolved actors, such as observed in the Rede Ecovida de Agroecologa reality.